Blur Out - Shin, Hye Rim (SURFACE at Syracuse University, 2017)
Blur Out explores ideas about architecture that seeks ephemerality rather than legibility, eidetic affects rather than demand of focused attention and atmospheric or emotional spaces rather than conventional spaces. The exploration of Blur Out is situated within the research topic of different states of snow that are generated from avalanche phenomena of Iceland, which develops site specific understandings of the phenomena and effects. The project aims to build a blurred boundary both literally and experientially between the built and natural environment to challenge representing and re-presenting the spectrum of tangibility to intangibility. By exploring the dichotomy between the built and the natural context of Iceland, a new understanding of perceiving and experiencing the avalanche phenomena creates an uncanny relationship that would change and draw attention from sublime as the norm to sublime as the spectacular.